2014
DOI: 10.1016/j.jebo.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Temporal spillovers in land conservation

Abstract: Abstract:Temporal spillovers occur when a conservation program preserves land during a contract period but shifts non-conservation use to later-or, worse, induces more intensive use later. This may happen when conservation improves land so that returns to other uses are increased. I explore temporal spillovers of the Conservation Reserve Program (CRP). I use a pre-analysis sample specification step to choose counterfactual land most like the CRP land. I find that CRP causes some land to be 22-27% more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…In addition, we summarized different types of financial incentives/disincentives and interactions among BMPs that have been neglected in the literature [80,82,87]. Factors shown to influence conservation adoption, and areas in which research is lacking, are listed in Table 3 and outlined in the following sections.…”
Section: Findings: Factors Influencing Bmp Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we summarized different types of financial incentives/disincentives and interactions among BMPs that have been neglected in the literature [80,82,87]. Factors shown to influence conservation adoption, and areas in which research is lacking, are listed in Table 3 and outlined in the following sections.…”
Section: Findings: Factors Influencing Bmp Adoptionmentioning
confidence: 99%
“…Other research has focused on the spatial slippage that occurs when conservation programs increase productive farm land scarcity and some less productive land is brought into production temporarily [122][123][124]. Temporal spillover has been examined by studying the impact of adoption of certain BMPs (such as enrollment in a conservation program) on the later adoption of other practices (such as staying in the same conservation program or switching to another program) [80]. She finds that CRP leads to land being 20-25% more likely to be farmed, potentially offsetting some environmental benefits.…”
Section: Interactions Among Bmps and Spatial And Temporal Spillover mentioning
confidence: 99%
“…Other enrolled parcels, however, have productive potential and are unlikely to stay in CRP long‐term. Jacobson (2014) found that, compared to similar fields that had never been enrolled in CRP, former CRP fields that were voluntarily removed from the program were 20–25% more likely to be farmed. The authors thus hypothesized that some landowners may use CRP “as a long, subsidized fallow period” (Jacobson, 2014, p.378).…”
Section: Discussionmentioning
confidence: 99%
“…Jacobson (2014) found that, compared to similar fields that had never been enrolled in CRP, former CRP fields that were voluntarily removed from the program were 20–25% more likely to be farmed. The authors thus hypothesized that some landowners may use CRP “as a long, subsidized fallow period” (Jacobson, 2014, p.378). Greater insight is needed into the social and biophysical conditions that prompt landowners to offer agriculturally productive fields for CRP enrollment and the programmatic conditions that lead FSA to grant these fields CRP contracts.…”
Section: Discussionmentioning
confidence: 99%
“…The literature points to optimal land use models, income growth and demand for forest products, corruption, costly enforcement, illegal logging, and other institutional weaknesses. 8 Alemagi and Kozak (2010) argue that several or 6 The estimated numbers of such leakage vary between 5 and 95 percent, but more typical estimates are around 40 percent (Atmadja and Verchot, 2012;Jacobson, 2014;Meyfroidt and Lambin, 2009;Murray, 2008;Murray et al, 2004) . 7 In Nepal, "the Forest Department was poorly sta¤ed and thus unable to implement and enforce the national policies, and deforestation increased in the 1960s and 1970s" (Shyamsundar and Ghate, 2014, pp.85).…”
Section: Introductionmentioning
confidence: 99%